INTERNALISASI PENDIDIKAN EMANSIPATORIS DI PERGURUAN TINGGI PESANTREN - Azfina Kurniyati; Ach. Nurholis Majid (Jurnal Inovasi Penelitian, 2021)
The high of drop out of school digit, pupil character decadence and social deviating which are happen in Indonesia be sigh education problematic. In the middle cases glow which is happen need solution by education strip especially Islamic boarding school to content those problems. IDIA with the excellent which it have, rules and system of IDIA are hoped can be agent of change in guiding pupil character and content which is happen this time. So this article will examine deeply about emancipatory education internalization values and method in IDIA Prenduan. Data in this research are collected by participant observation, interview and documentation method. Those data, then are analyzed by Miles and Huberman model analyzes. This research result show, that emancipatory education in the high Islamic boarding school which is pointed to educate university student awareness about right and obligation reasonably based on Islamic, ma’hadi and tarbawi values. Internalization process executed by exemplary, discipline, practice and habituation, rewards and punishments and ibrah and mauidzah hasanah methods.